(untitled) (Semiárida, 2020)
In the region of “Espinal”, Calden District in the province of San Luis there is a strong agriculturization process with the consequent loss of native forest remnants, conserving endangered native species and invasion of exotic species. The aim of this study was to evaluate the effect of the stripe clearing on 6 species of caldenal (4 grasses and 2 broadleaves). The study was conducted in a field 15 km to the north of the city of Villa Mercedes (San Luis), subjected to a strip-clearing for agricultural use, in the year 2003. On 5 sites into native forest remnants stripes and 5 into without clearing native forest, 39 m long transects were laid, N-S direction, and along the same were recorded the presente species in 14 sampling units of 1 m2. Data were analyzed by IBM SPSS Statistics 19, through nonparametric methods, Mann-Whitney U. Statistical analysis showed significant differences (p <0.05) in Digitaria californica, Pappophorum pappiferum, Salsola kali and Cestrum parqui. The study showed that the cultivation of native forest between stripes was a change in the frequency of native grasses and broadleaves.